Cluster of differentiation 44 promotes osteosarcoma progression in mice lacking the tumor suppressor Merlin. Issue 9 (23rd June 2020) - Ma, Junzhi; Klemm, Janina; Gerardo‐Ramírez, Monserrat; Frappart, Lucien; Castven, Darko; Becker, Diana; Zoch, Ansgar; Parent, Romain; Bartosch, Birke; Minnich, Kerstin; Giovannini, Marco; Danckwardt, Sven; et al.
Abstract: Merlin is a versatile tumor suppressor protein encoded by the NF2 gene. Several lines of evidence suggest that Merlin exerts its tumor suppressor activity, at least in part, by forming an inhibitory complex with cluster of differentiation 44 (CD44). Consistently, numerous NF2 mutations in cancer patients are predicted to perturb the interaction of Merlin with CD44. We hypothesized that disruption of the Merlin‐CD44 complex through loss of Merlin, unleashes putative tumor‐ or metastasis‐promoting functions of CD44. To evaluate the relevance of the Merlin‐CD44 interaction in vivo, we compared tumor growth and progression in Cd44 ‐positive and Cd44 ‐negative Nf2 ‐mutant mice. Heterozygous Nf2‐ mutant mice were prone to developing highly metastatic osteosarcomas. Importantly, while the absence of the Cd44 gene had no effect on the frequency of primary osteosarcoma development, it strongly diminished osteosarcoma metastasis formation in the Nf2‐ mutant mice. In vitro assays identified transendothelial migration as the most prominent cellular phenotype dependent on CD44. Adhesion to endothelial cells was blocked by interfering with integrin α4β1 (very late antigen‐4, VLA‐4) on osteosarcoma cells and CD44 upregulated levels of integrin VLA‐4 β1 subunit. Among other putative functions of CD44, which may contribute to the metastatic behavior, the passage through the endothelial cells also appears to be critical in vivo, as CD44 significantly promoted formation of lung metastasis upon intravenous injection of osteosarcoma cells into immunocompromised mice. Altogether, our results strongly suggest that CD44 plays a metastasis‐promoting role in the absence of Merlin. Abstract : What's new? The protein Merlin acts as a tumor suppressor by forming a complex with CD44. Inactivating Merlin appears to allow CD44 to induce metastasis. Here, the authors looked at tumor growth and progression in osteosarcoma‐prone mice without functional Merlin protein, either with or without CD44. The loss of CD44 did not affect the formation of primary osteosarcomas, but did reduce the rate of metastasis. They then showed that CD44 regulates integrin α4β1 to enhance attachment of tumor cells to endothelial cells and promote migration and metastasis.